Henry and Mudge and the Great Grandpas : The Twenty-sixth Book of Their Adventures - Rylant, Cynthia; Stevenson, Sucie (New York : Simon & Schuster Books for Young Readers, 2005)
When Henry and his dog Mudge go with Henry's parents to visit Great-Grandpa Bill in the home with lots of other grandpas, they lead them all on a wonderful adventure.
Ages 5-7.